Undergraduate Perception on Effect of Drug Abuse on Academic Performance of Students Using UNN as Study Area - Nnadi, Helen; Nwankwo, Christopher EMMANUEL; CHINWEOKWU, Narcel Joy (Unisia, 2025)
This study examined undergraduate perceptions of the effect of drug abuse on students' academic performance at the University of Nigeria, Nsukka. Guided by two research objectives and two hypotheses, the study adopted a cross-sectional survey design, utilizing multi-stage random sampling to select 200 respondents. Data was collected through a structured questionnaire and analyzed using SPSS. The findings revealed that drug abuse negatively affected students' academic engagement; some students reported that drug use initially enhanced alertness, but it eventually led to a decline in academic performance due to absenteeism, poor time management, and reduced participation in group activities. Given these findings, it was recommended that universities implement stricter anti-drug policies alongside awareness campaigns highlighting the academic risks of substance abuse. Counseling services should be strengthened to support students struggling with drug-related challenges, and peer mentorship programs should be introduced to promote positive academic behaviors and discourage substance abuse.